2020
DOI: 10.2478/dcse-2020-0023
|View full text |Cite
|
Sign up to set email alerts
|

Examining Teachers’ Culturally Relevant Education Self-Efficacy Perceptions in Turkey

Abstract: We designed this study with the aim to examine teachers’ culturally relevant and sustaining education self-efficacy perceptions in Turkey. For this purpose, we developed a Culturally Relevant/Sustaining Education Self-Efficacy Scale. We obtained the data from 1302 teachers. Data analysis proceeded in three steps: First, we analyzed factor analysis. Second, we conducted a descriptive analysis of the items on the CRESE Scale. Finally, we compared teachers’ perceptions. The scale consists of a single factor and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…In addition, it has been found that as time spent in culturally diverse classroom increases, teachers’ burnout increases if they have low self-efficacy in managing the culturally diverse classroom and designing the learning process (Gutentag et al, 2018). Furthermore, research (Alev, 2018; Kotluk, 2018; Telef, 2011; Yildirim & Ilhan, 2010) shows that teachers can achieve success and a positive mood when their general self-efficacy is high, that they are persistent and diligent in the teaching process and that they do not give up in the face of failure. As can be understood from the literature, teachers should have a high general self-efficacy belief in order to exhibit culturally responsive teacher behavior.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, it has been found that as time spent in culturally diverse classroom increases, teachers’ burnout increases if they have low self-efficacy in managing the culturally diverse classroom and designing the learning process (Gutentag et al, 2018). Furthermore, research (Alev, 2018; Kotluk, 2018; Telef, 2011; Yildirim & Ilhan, 2010) shows that teachers can achieve success and a positive mood when their general self-efficacy is high, that they are persistent and diligent in the teaching process and that they do not give up in the face of failure. As can be understood from the literature, teachers should have a high general self-efficacy belief in order to exhibit culturally responsive teacher behavior.…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, they have the perception that they can design teaching processes according to cultural differences (Siwatu et al, 2016(Siwatu et al, , 2017. In a study conducted by Kotluk (2018), teachers' views on culturally responsive education are highly positive. However, the teachers stated that they felt inadequate designing a course according to cultural differences in the teaching process.…”
Section: General Self-efficacymentioning
confidence: 99%
See 1 more Smart Citation
“…The improvement of professional proficiency can be achieved, for instance, through programs in multicultural education (Choi & Mao, 2021), or by experiences with cultural and linguistic diversity gained through studying or working abroad (Park et al, 2016). Kotluk and Kocakaya (2020) conclude that perceptions of professional proficiency are shaped by broader contexts that pertain to teachers' academic and demographic characteristics. The authors suggest that, in addition to teachers' experience with multicultural education, perceptions of their own professional efficacy vary with teachers' age, the length of their teaching experience, the quality of the program's teachers have completed in their undergraduate and graduate preparation, the location where teachers work, as well as the subjects they teach.…”
Section: Theoretical Background and Literature Reviewmentioning
confidence: 93%
“…Accordingly, teacher intercultural self-efficacy comprises teachers' confidence to execute a range of tasks, such as reducing prejudice towards people from different cultural or ethnic groups (Guyton & Wesche, 2005), using examples that are familiar to students from diverse cultural or ethnic backgrounds (Siwatu, 2007), and creating a warm and safe classroom environment that respects all cultures (Siwatu et al, 2017). While most research on intercultural self-efficacy was conducted in the US, recently, teacher intercultural self-efficacy has also been examined in other national contexts like South Korea (Roh, 2015) Germany , Taiwan (Chu, 2011), and Turkey (Kotluk & Kocakaya, 2020).…”
Section: Teacher Intercultural Self-efficacymentioning
confidence: 99%